Pengaruh Kepribadian Dan Gaya Hidup Terhadap Keputusan Pembelian Pada Produk Ventela Shoes Di Kota Bima - M. Hisyam Risqullah; Haryanti, Intisari (Pusat Riset dan Inovasi Nasional, 2026)
This research was conducted on Ventela Shoes Consumers in Bima City. With the aim of determining the influence of personality and lifestyle on purchasing Ventela Shoes products in Bima City. The population in this study were Bima City residents who had purchased Ventela Shoes products several times. While the sample in this study was 96 respondents. Data analysis used was validity test, reliability test, classical assumption test, multiple linear regression test, correlation coefficient test, determination coefficient test, partial t test, and f test. The results of this study indicate that Personality and Lifestyle variables simultaneously influence purchasing decisions for Ventela Shoes products in Bima City. Keywords: Personality, Lifestyle, Purchasing Decisions